IFRS adoption, corporate governance, investor protection and earnings quality in Malaysian listed companies - Alhadi, Saleh M. A. Abd (2019)
Earnings quality (EQ) is a vital indicator for financial reporting users. However, the existence of accrual-based (ACEM) and real earnings management (TREM) might distort EQ. This thesis has four objectives. First, it intends to investigate EQ changes among different types of firm ownership pre and post IFRS adoption. Second, it attempts to determine the relationship between board of directors (i.e. multiple directorships, social title, board effectiveness and audit committee (AC) effectiveness), ownership structure (i.e. managerial, institutional, family, and politically-connected (PC) ownership), and EQ. Third, it examines the moderating effect of IFRS on the link between corporate governance (CG) mechanisms and EQ. Finally, this research investigates the moderating role of investor protection (INP) on the relationship between CG and EQ. The study used a sample of 209 non-financial companies listed on the Bursa Malaysia during the period of 2007 to 2016. It also employed the Paired t-test to achieve the first objective and the Generalized Method of Moments (GMM) for the rest of the objectives. The results indicate that managerial, institutional, and family ownership provide an appropriate environment and strengthen IFRS effectiveness in reducing ACEM. Also, both the board and ownership characteristics significantly influence EQ indicators. This study finds that multiple directorships, AC effectiveness, and PC ownership significantly reduce both ACEM and TREM, while the rest influence only one of the earnings management indicators. After IFRS, ownership structure plays a major role in improving the firm's EQ. More importantly, the monitoring role of board and AC attributes are more efficient in a healthy INP environment. Policymakers should realise that developing accounting standards alone will not be able to improve EQ per se. In addition, accounting and law enforcements are essential in fighting corporate misbehaviours. As ownership concentration can substitute the monitoring mechanism (which may backfire), alternative characteristics of good governance, such as, INP are indispensable.